Urban morphology and accessibility classification as supportive data for disaster mitigation in Chiang Mai, Thailand - N. Srinurak; N. Mishima; A.N. Kakon (International Association of Lowland Technology, 2016)
In historic town, investigation on limitations of streets to provide countermeasure during an evacuation is recently in concern. This study objective is to classify labyrinth and narrowness of urban accessibility that comprise with its urban morphology. The study area is Chiang Mai’s historic town locate in northern of Thailand. To identify risk level of the street, egress point from buildings were surveyed and collected combine with street width as urban accessibility factors. Urban morphologyof street network identified using space syntax integrations analysis. Additionally, Egress point locations also analysed using kernel density mapping to revealed risk level as area type and finally compared with classified streets map created by Hierarchy Cluster Analysis. The result shows classification of streets;Substreets were subdivided into Priorities streets determined by its level of risk. Priorities streets revealed a risk of bottlenecks caused by narrowness and high egress points ratio. Classification map shows crucial supportive data to evacuate strategies in disaster mitigation of historic town characters.